2012
DOI: 10.1007/s00192-011-1650-6
|View full text |Cite
|
Sign up to set email alerts
|

Cystocele repair by vaginal route: comparison of three different surgical techniques of mesh placement

Abstract: RP technique is less effective than TO and FG techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
1
3
0
1
Order By: Relevance
“…Our study showed that even with conventional cystocele repair, with an appropriate reinforcing method it is possible to achieve excellent results in the repair of cystocele. Furthermore, in the long-term follow-up, the incidence of postoperative complications compared favourably with previously published results for conventional or mesh studies [7,11]. Thus, our method of conventional cystocele repair with purse-string and simple, additive reinforced sutures compared favorably with previous conventional or mesh studies, showed no recurrence of cystocele, and showed no increased postoperative voiding problems.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our study showed that even with conventional cystocele repair, with an appropriate reinforcing method it is possible to achieve excellent results in the repair of cystocele. Furthermore, in the long-term follow-up, the incidence of postoperative complications compared favourably with previously published results for conventional or mesh studies [7,11]. Thus, our method of conventional cystocele repair with purse-string and simple, additive reinforced sutures compared favorably with previous conventional or mesh studies, showed no recurrence of cystocele, and showed no increased postoperative voiding problems.…”
Section: Discussionsupporting
confidence: 77%
“…Because of the known high failure rate of conventional methods, use of a graft or mesh as a reinforcing material has been popularized, but specific complications related to these procedures have begun to be clarified. Such complications include erosion, infection, contraction, de novo dyspareunia, and chronic pain [6,10,11]. Our study showed that even with conventional cystocele repair, with an appropriate reinforcing method it is possible to achieve excellent results in the repair of cystocele.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The use of large vaginal meshes for the treatment of pelvic organ prolapse (POP) in combination with poor surgical experience are the dominating risk factors for serious postoperative complications. [1][2][3] Reducing the amount of implanted material is one of the most important criteria for success in the treatment of POP. Vaginal meshes have undergone significant changes over time, which are still happening today.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Respecto de los tiempos de evaluación de la CVRS, han sido determinados en función de los cambios esperados en el postoperatorio, existiendo cambios en el seguimiento a los tres, seis, 12 y 24 meses principalmente (57,101,(128)(129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140) . Actualmente ha aumentado la evidencia de seguimiento a cinco o más años (102,128,(140)(141)(142)(143) .…”
Section: Ii22 Instrumentos De Medición De La Cvrs En Mujeres Con Popunclassified